Does gender diversity moderate the relationship between supply chain management practice and performance in the electronic manufacturing services industry? - Chin, Thoo Ai (Taylor and Francis Inc., 2015)
This study attempts to examine the moderating effects of gender diversity on the relationship between supply chain management (SCM) practices and supply chain performance in the Malaysian electronic manufacturing services (EMS) industry. The respondents were selected from the four departments: purchasing, planning, logistics and operation of one of the most well-known Malaysian manufacturing company located in Johor state, Malaysia; with the questionnaires being distributed via email. Hierarchical regression analysis was used to test the above objective. Findings indicate that SCM practices–performance relationship was not moderated by employees’ gender diversity. Theoretical and managerial implications as well as conclusion are also explored.